2014
DOI: 10.1042/bj20140494
|View full text |Cite
|
Sign up to set email alerts
|

N-terminus of the protein kinase CLK1 induces SR protein hyperphosphorylation

Abstract: SR proteins are essential splicing factors that are regulated through multisite phosphorylation of their RS (arginine-serine-rich) domains by two major families of protein kinases. The SRPKs efficiently phosphorylate the arginine-serine dipeptides in the RS domain using a conserved docking groove in the kinase domain. In contrast, CLKs lack a docking groove and phosphorylate both arginine-serine and serine-proline dipeptides, modifications that generate a hyper-phosphorylated state important for unique SR prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 29 publications
4
59
0
Order By: Relevance
“…Furthermore, we showed that the N-terminus also interacts with its kinase domain but is not a substrate, suggesting that it can bind different proteins in intra- and intermolecular fashions (Aubol et al, 2014; Colwill et al, 1996). To determine whether the CLK N-terminus also interacts with SRPK, we performed in vitro pull-down experiments using GST-tagged SRPK1 with either full-length His-tagged CLK1 or a form lacking its N-terminus (CLK1(ΔN)).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, we showed that the N-terminus also interacts with its kinase domain but is not a substrate, suggesting that it can bind different proteins in intra- and intermolecular fashions (Aubol et al, 2014; Colwill et al, 1996). To determine whether the CLK N-terminus also interacts with SRPK, we performed in vitro pull-down experiments using GST-tagged SRPK1 with either full-length His-tagged CLK1 or a form lacking its N-terminus (CLK1(ΔN)).…”
Section: Resultsmentioning
confidence: 98%
“…We showed previously that the CLK1 N-terminus binds with high affinity to the RS domain of its substrate SRSF1 (Aubol et al, 2014). Furthermore, we showed that the N-terminus also interacts with its kinase domain but is not a substrate, suggesting that it can bind different proteins in intra- and intermolecular fashions (Aubol et al, 2014; Colwill et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One prior report identified EWS-FLI1 increasing TERT activity independently of DNA binding; however, no isoform analysis was performed (56). These four genes were recognized as putative contributors to oncogenesis based on the published literature (57)(58)(59)(60)(61)(62)(63)(64)(65). None of these genes were alternatively spliced by WT EWS reduction.…”
Section: Yk-4-279 Alters Splicing Rather Than Direct Transcriptionalmentioning
confidence: 99%
“…Tra2␤1 constructs (1 M) were incubated with SRPK1 (200 nM) and 0.3 mM ATP in 25 mM Mops (pH 7.2) and 10 mM free Mg 2ϩ for 10 min or 2 h in a total volume of 100 l. Reaction quenching and desalting were performed according to a prior method (34). The binding of RNA to the Tra2 proteins was measured using a nitrocellulose membrane and a Bio-Dot apparatus (Bio-Rad) according to a previously published protocol (36).…”
Section: Methodsmentioning
confidence: 99%